2019
DOI: 10.1007/s12105-019-01034-0
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Duct Carcinoma of the Parotid Gland Originating from an Epithelial-Myoepithelial Carcinoma: Report of a Rare Case

Abstract: Salivary duct carcinoma (SDC) is a high-grade carcinoma with poor prognosis, especially among various salivary carcinomas. In this study, we report a rare case of SDC of the parotid gland originating from an epithelial-myoepithelial carcinoma (EMC). A 71-year-old Japanese man presented with swelling of the right parotid region and a right facial nerve paralysis for 10 months. He underwent extended total parotidectomy and chemoradiotherapy after the surgery. Histologically, a major part of the tumor was an andr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…If one component of a suspected HC has high proliferative activity and the other has low proliferative activity, carcinoma with HGT should also be considered [32] As both components exhibited similar levels of proliferative activity in all of our cases, we considered that they were not carcinomas with HGT. Recently, Hamamoto et al reported a rare case in which SDC arose from EMC, and they considered that their case should be diagnosed as HC rather than carcinoma with HGT, despite the fact that the two components displayed different proliferative activities and histological grades [23]. Our case 3 might have undergone a similar tumorigenic process to their case.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…If one component of a suspected HC has high proliferative activity and the other has low proliferative activity, carcinoma with HGT should also be considered [32] As both components exhibited similar levels of proliferative activity in all of our cases, we considered that they were not carcinomas with HGT. Recently, Hamamoto et al reported a rare case in which SDC arose from EMC, and they considered that their case should be diagnosed as HC rather than carcinoma with HGT, despite the fact that the two components displayed different proliferative activities and histological grades [23]. Our case 3 might have undergone a similar tumorigenic process to their case.…”
Section: Discussionmentioning
confidence: 52%
“…Although little information is available, several investigators have suggested that the aggressiveness of HC is determined by the histologically higher-grade component. 23 It would appear that treatments for HC should be targeted at the higher-grade component, but this requires further con rmation in much larger series with longer follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamamoto et al. reported that their case had SDC and EMC components and inner ductal cells of double-layered EMC ducts with a similar morphology and immunophenotype to the SDC in the transitional area and suggested that a SDC originated from the EMC inner ductal cells [ 9 ]. We believe that our case was similar; however, the relationship between MC and EMC/SDC is unclear whether hybrid carcinoma or HGT.…”
Section: Discussionmentioning
confidence: 99%
“…There have been case reports of other types of malignancies like adenoid cystic carcinoma existing along with EMC in salivary glands [6] . Hamamoto et al 2019 published a case report of a ductal carcinoma arising from an existing EMC in the parotid gland [7] . In a study conducted by Gore in 2018, 468 patients were identified with EMC during the time period from 1973-2014.…”
Section: Introductionmentioning
confidence: 99%